(untitled) (REVISTA NODO, 2026)
The Future City: Utopian and Dystopian Panoramas is a pictorial research-creation project undertaken with the support of the National System of Art Creators, granted by the Ministry of Culture of the Government of Mexico, through the System of Support for Creation and Cultural Projects (SACPC). It consists of the creation of fictional panoramas of the future of Mexico City, based on photographic records from a series of ethnographic field trips, as well as press images and personal drawings.